The impact of banking behaviour on monetary strategy - Manfred Borchert (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2004)
At present, Western European banks are increasingly branching out into asset management as well as the consulting business, which cannot be influenced directly by monetary controls. We have therefore conducted a factor analysis of banks' balance-sheet items, and we have also plotted figures from banks' income statements. Our analyses fulfil a triple purpose. First, they shed much light on the positioning strategies deployed by European banks. Secondly, they reveal various tendencies in respect of the refinancing strategies that are adopted when credits are granted to non-banks. Thirdly, they facilitate an assessment of the effectiveness of monetary policy. There is clear evidence that the European Central Bank's money supply policy will prove progressively less efficient as banks resort increasingly to refinancing by assets and continue to expand their banking services by building up their consulting businesses.
Keywords: E50; E51; E58; G21; 330; Banking structure; Banking market; Banks' business strategies